Environmental Concern Over Time: Evidence from the Longitudinal Analysis of a British Cohort Study from 1991 to 2008*. (22nd July 2014) - Melis, Gabriella; Elliot, Mark; Shryane, Nick
<x xml:space="preserve">Abstract</x> Objective We examined whether and how levels of environmental concern (EC) changed over time in the United Kingdom, from 1991 to 2008–2009, as well as how EC relates to socioeconomic characteristics across this same timeframe. Methods Using item response theory models on the last three sweeps of the British National Child Development Study 1958, we evaluated a measure of EC. Then, using latent growth curve models (LGCMs) we estimated the pattern of change for EC across time. Finally, theoretically relevant sociodemographic characteristics were introduced as covariates into the LGCM. Results We found a small but significant downfall of the mean level of EC over time, with individual‐level values displaying higher dispersion in 2008–2009 against the previous sweeps of data. We also found that political orientation has significant effects on the outcome and on its changes across time. Conclusions Hypotheses regarding the influence of interest in politics and voting choices on EC are supported. The increasing variance of EC over time warrants further investigation.